Pengaruh Kualitas Produk, Kualitas Layanan, Dan Harga Terhadap Keputusan Pembelian Konsumen Coffee Shop “Gula Kopi” - Purnama, Oka (PERFORMA, 2023)
Food and beverage industry has high level business competition due to the large number of entrepreneurs. Food and beverage entrepreneurs must be able to provide the best for consumers in order to be outstanding in competition. Entrepreneurs must be able to understand the factors that influence consumers’ purchasing decision, such as product quality, service quality, price, and others. This research is done to find out the influence of product quality, service quality, and price on purchasing decision of "Gula Kopi" coffee shop consumers. This research uses quantitative method by analyzing the population of "Gula Kopi" coffee shop consumers. This research uses purposive sampling technique which is distributed to 97 respondents with the criteria respondents whose age at least 17 years old who have ever shopped at "Gula Kopi" coffee shop at least once. Data collection in this research uses questionnaire help that is distributed through Google form by applying Likert scale 1-5 to answer statements based on the level of agreement or on the contrary. Data analysis in this research uses SPSS application to be able to do the series of multiple linear regression test. The result of this research indicates that the variables of service quality and price do not influence significant on purchasing decision, while product quality variable influences significant on purchasing decision of “Gula Kopi”coffee shop consumers.